PENGARUH PRODUK, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK POCKY DI SURABAYA BARAT - Eriana Nur Risqi Ananda; Hendrik Rizqiawan (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to analyze the influence of Product, Promotion and Price on Repurchase Decision. The sample in this study is consumers who are at least 17 years old and have purchased Pocky Products in West Surabaya. The sampling technique in this study used a non-probability sampling technique in the form of purposive sampling with a total of 74 respondents. Data mining was carried out using questionnaires, responses from respondents were analyzed using the Statistical Product and Service Solutions (SPSS) program version 21. This study used multiple linear regression analysis. Hypothesis testing is performed partially (t-test) and simultaneously (F-test). The results of this study show that the Product, and Price do not have a significant effect while the Promotion partially and simultaneously has a positive and significant effect on the Repurchase Decision of Pocky Products in West Surabaya.